Counseling on the Dangers of Repeated Use of Cooking Oil and Training on the Valorization of Used Cooking Oil for Dorokdok Cracker Producer in Suci Village - Fauziah, Nenden; Prasetiawati, Riska; Senania, Astri; Apriani, Riza; Annisa Rahmasari Kanto, Dhini (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2024)
Producers of cowhide crackers (dorokdok) in Suci Village have the potential to produce cooking oil waste of more than 1 ton/week. In addition, cooking oil is often used repeatedly to reduce production costs. From situation analysis and field observations, the people of Suci Village do not yet know the dangers of using used cooking oil repeatedly and how to process used cooking oil into biodiesel. This service activity aims to educate the public about the dangers of repeated use of used cooking oil and the valorization of used cooking oil into biodiesel. It is hoped that the step of valorizing used cooking oil can prevent repeated use of cooking oil without having an impact on increasing dorokdok production costs. The method of implementing service is counselling and training. Changes in community knowledge are evaluated through the implementation of pretests and posttests. The evaluation results show an increase in public knowledge about the dangers of repeated use of cooking oil and steps to valorize used cooking oil reaching 66.20%. It is hoped that the step to valorize used cooking oil will be a way to create a healthy environment and food as well as realize economic independence in Suci Village.